2018
DOI: 10.1002/cbf.3353
|View full text |Cite|
|
Sign up to set email alerts
|

Insulin‐like growth factor binding protein 4 inhibits proliferation of bone marrow mesenchymal stem cells and enhances growth of neurospheres derived from the stem cells

Abstract: Insulin-like growth factor binding protein 4 (IGFBP-4) was reported to trigger cellular senescence and reduce cell growth of bone marrow mesenchymal stem cells (BMSCs), but its contribution to neurogenic differentiation of BMSCs remains unknown. In the present study, BMSCs were isolated from the femur and tibia of young rats to investigate effects of IGFBP-4 on BMSC proliferation and growth of neurospheres derived from BMSCs. Bone marrow mesenchymal stem cell proliferation was assessed using CCK-8 after treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…MGP promoted the bone formation by activating the Wnt/β-catenin pathway ( 22 ). IGFBP4 reduced the proliferation of BMMSCs, thus inhibiting excessive osteogenic differentiation in rats ( 23 , 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…MGP promoted the bone formation by activating the Wnt/β-catenin pathway ( 22 ). IGFBP4 reduced the proliferation of BMMSCs, thus inhibiting excessive osteogenic differentiation in rats ( 23 , 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…IGFBP4 plays an important role in bone metabolism and participates in senescent-associated processes in MSCs [ 60 , 61 ]. We showed that IGFBP4 expression in both H- and P-GMSCs was not modified by P. gingivalis .…”
Section: Discussionmentioning
confidence: 99%
“…Cells grew in a typical fusiform morphology and spindle-shaped ( Fig. 1A), which is a common form of mesenchymal stem cells [31]. It was found that Oil red O staining were positive after adipogenic differentiation (Fig.…”
Section: Phenotype and Differentiation Ability Of Bmscmentioning
confidence: 96%